2010
DOI: 10.1063/1.3480602
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic etching of diamond by molten Ni particles

Abstract: Nanopores in insulating solid state membranes have recently attracted much interest in the field of probing, characterizing, and manipulating single linear polymers such as DNA/RNA and proteins in their native environment. Here a low cost, fast, and effective way to produce nanostructures such as pyramidal shaped nanopores and nanochannels with dimensions down to about 15 nm in diamond membranes without any need for electron-beam lithography is demonstrated. By use of a catalytic process, anisotropic etching o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…It has been shown that Ni-assisted diamond etching is slowest for the [111]-oriented diamond planes and that they act as stopping planes [13]. Since the uptake of carbon atoms from diamond by the metal nanoparticles occurs from the weakly bonded atoms, the carbon atoms of the closest packing plane, the {111} planes, are the most stable against the dissolution of carbon in nanoparticles, as compared to the other crystal planes [30].…”
Section: Effect Of Diamond Microstructurementioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that Ni-assisted diamond etching is slowest for the [111]-oriented diamond planes and that they act as stopping planes [13]. Since the uptake of carbon atoms from diamond by the metal nanoparticles occurs from the weakly bonded atoms, the carbon atoms of the closest packing plane, the {111} planes, are the most stable against the dissolution of carbon in nanoparticles, as compared to the other crystal planes [30].…”
Section: Effect Of Diamond Microstructurementioning
confidence: 99%
“…The orientation dependence of diamond etching has been studied before using molten Ce [28], Fe particles [29], Co nanoparticles [30], and molten Ni [13], as catalysts. It has been shown that Ni-assisted diamond etching is slowest for the [111]-oriented diamond planes and that they act as stopping planes [13].…”
Section: Effect Of Diamond Microstructurementioning
confidence: 99%
See 2 more Smart Citations
“…To produce boron-doped diamond based structures, reactive ion etching of the wafer (Fig. 9.2d) is conducted in a gas mixture of oxygen and hydrogen [58]. Please note that these structures are protected.…”
Section: Diamond Micro-and Ultramicro-electrode Arraysmentioning
confidence: 99%